How Forgiveness Affects Teacher Life Satisfaction Mediated by Teacher Gratitude? - Ponco Dewi Karyaningsih; Susan Febriantina; Roni Faslah Munawaroh; Munawaroh; Farah Cantika (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
Abstract: This study aims to determine the effect of forgiveness on teacher life satisfaction mediated by gratitude at vocational high school teachers in Tangerang District. This survey research with a sample of 205 respondents, uses proportionate random sampling techniques. The data were analyzed using SmartPLS 3.0 program, and a detection test of intervening variables effect uses multiple tests. Our findings show that forgiveness affects the life satisfaction of teachers as mediated by gratitude. The original sample value of the influence of these three variables is 0.230 and t-statistics> 1.96 is 4.192. Furthermore, based on a p-value of 0.000 <0.05, the forgiveness variable influences life satisfaction with gratitude as mediation, which has a significant indirect effect. The Sobel test results got a value of 4.757, the values > 1.96, this proves that gratitude can mediate the effect of forgiveness on teacher life satisfaction. This study can encourage social and human scientific development efforts. Keywords: forgiveness, life satisfaction, gratitude.